Literature Review: Perbandingan Tingkat Kesembuhan Luka Bakar dengan Pemberian Madu pada Berbagai Jenis Tikus - Anggoro Dwi Laksono (Fakultas Ilmu-ilmu Kesehatan Universitas Jenderal Soedirman, 2021)
Introduction: Burns are a serious health problem and are often faced by doctors. Various studies show that honey is effective in healing burns. Honey is thought to act as an antibacterial and is now being used as a treatment burn victims. Aim: this study aims to review some literature on management by using honey to heal burns tested in rat. Method: Article searches conducted electronically in some databases: Sage database, PubMed, Science Direct, Mendeley, and Google Scholar, by 2007 until 2017. Keywords used were “Burn”, “Honey”, “Rat”; and finally got six articles matched. Result: Interventions using honey can be used and effective in curing burns. Discussion: The use of honey for combined effective burns in accelerating the healing process of tissue in the wounded area. The honey intervention method for burns should be further improved and implemented as a treatment for burns. Conclusion: Honey is very effective to accelerate and heal burns.